Flexible Pressure Sensor with Tunable Sensitivity and a Wide Sensing Range, Featuring a Bilayer Porous Structure - Yunjiang Yin; Yingying Zhao; Tao Xue; Xinyi Wang; Qiang Zou (Micromachines)
Flexible piezoresistive pressure sensors have great potential in wearable electronics due to their simple structure, low cost, and ease of fabrication. Porous polymer materials, with their highly deformable internal pores, effectively expand the sensing range. However, a single-sized pore structure struggles to achieve both high sensitivity and a broad sensing range simultaneously. In this study, a PDMS-based flexible pressure sensor with a bilayer porous structure (BLPS) was successfully fabricated using clamping compression and a sacrificial template method with spherical sucrose cores. The resulting sensor exhibits highly uniform pore sizes, thereby improving performance consistency. Furthermore, since different pore sizes and thicknesses correspond to varying Young’s moduli, this study achieves tunable sensitivity across a wide pressure range by adjusting the bilayer thickness ratio (maximum sensitivity of <semantics>0.063 kPa−1</semantics> in the 0–23.6 kPa range, with a pressure response range of 0–654 kPa). The sensor also demonstrates a fast response time (128 ms) and excellent fatigue stability (>10,000 cycles). Additionally, this sensor holds great application potential for facial expression monitoring, joint motion detection, pressure distribution matrices, and Morse code communication.